Linking individualistic growth stability of trees to the complexity of understorey layers - Zheng, Jiacheng; Lyu, Lixin; Zhong, Yuan; Yang, Jing; Qiu, Hongyan; Zhang, Qi‐Bin (The Journal of ecology, 2025)
Tree‐growth stability is crucial in upholding forest ecosystem services. Despite extensive research on the correlation between tree growth and climate, the influence of forest understorey on tree‐growth stability remains understudied. We surveyed forest plots and collected tree‐ring samples along two elevational gradients, ranging from 3600 to 4400 m a.s.l., in the southeastern Tibetan Plateau. An index was developed to quantify individualistic growth stability of trees, and its linkage with the complexity of forest understorey structure was examined. We found that tree‐growth stability is more pronounced in complex forest communities. In forests with higher understorey complexity, the proportion of trees experiencing growth release increased during wet years, while those with growth suppression augmented during dry years. Interestingly, a subset of trees exhibits abnormal growth increases even during the driest years, whereas another subset shows abnormal growth reductions during the wettest years. Furthermore, forests with more complex understorey structures exhibited a higher proportion of trees showcasing these two types of ‘anti‐phase’ growth statuses. Synthesis. Our study underscores the linkage between individualistic growth stability of trees and the complexity of understorey structures. The growth stability of the overstorey layer is conveyed at the expense of individual‐level growth stability and synchrony in forests with complex understorey structures. These findings emphasize the necessity for attention to the interplay between tree growth and understorey community structures when assessing the impacts of future climate change on forest dynamics. The complexity of understorey vegetation structures was found to exert a negative effect on the temporal stability of tree growth for two keystone tree species on the Tibetan plateau. Furthermore, group‐level stability of the overstorey layer is likely to be maintained at the expense of individual‐level growth stability and synchrony in forests with complex understorey structures.